Field reconstruction from proton radiography of intense laser driven magnetic reconnection - Palmer, CAJ; Campbell, PT; Ma, Y; Antonelli, L; Bott, AFA; Gregori, G; Halliday, J; Katzir, Y; Kordell, P; Krushelnick, K; Lebedev, SV; Montgomery, E; et al. (AIP Publishing, 2019)
Magnetic reconnection is a process that contributes significantly to plasma dynamics and energy transfer in a wide range of plasma and magnetic field regimes, including inertial confinement fusion experiments, stellar coronae, and compact, highly magnetized objects like neutron stars. Laboratory experiments in different regimes can help refine, expand, and test the applicability of theoretical models to describe reconnection. Laser-plasma experiments exploring magnetic reconnection at a moderate intensity (IL ∼1014 W cm-2) have been performed previously, where the Biermann battery effect self-generates magnetic fields and the field dynamics studied using proton radiography. At high laser intensities (ILλL2>1018 Wcm-2μm2), relativistic surface currents and the time-varying electric sheath fields generate the azimuthal magnetic fields. Numerical modeling of these intensities has shown the conditions that within the magnetic field region can reach the threshold where the magnetic energy can exceed the rest mass energy such that σcold = B2/(μ0nemec2) > 1 [A. E. Raymond et al., Phys. Rev. E 98, 043207 (2018)]. Presented here is the analysis of the proton radiography of a high-intensity (∼1018 W cm-2) laser driven magnetic reconnection geometry. The path integrated magnetic fields are recovered using a "field-reconstruction algorithm" to quantify the field strengths, geometry, and evolution.